Os Saberes Pedagógicos dos Professores do Ensino Superior: o cotidiano de suas práticas. - Simões., Mara Leite (2010)
This study is a Doctorate s thesis which had the aim to investigate the pedagogical knowledge of High Education professors: their daily practices, especially those professors from the Mathematics Course of the CCEN of UFPB. We developed a quanti-qualitative research of field and bibliographical nature. Our theoretical reference: Nóvoa (1995), Zabalza (2004), Perrenoud (1993, 2001, 2002), Pimenta and Anastasiou (2002), Masetto (1996, 1998, 2003), Morosini (2001), Tardif (1999, 2000, 2002, 2007, 2008), Charlot (2005), Imbernón (2000), Vasconcelos (1996, 1998, 2006), Ramalho (2004), Rodrigues (2003, 2004, 2006), among others who research professor s formation in regard to High Education teaching. With respect to the specific formation of the Mathematics professor as well as Mathematics Education, we analyzed Cury (2001), D Ambrosio B. (1993), D Ambrosio U. (1997), Balzan (1999), Fiorentini (1994), Bicudo (1996, 1999), Polettini (1999), among others. In order to deepen the knowledge concept, we used Morin s principles (1999, 2000, 2001, 2002, 2004, 2004a, 2004b, 2006a, 2006b, 2007a, 2007b, 2008). As concerns the post-modern education viewpoint, we employed the fundamentals of Pourtois and Desmet (1999) and Moraes (1997).With regard to education history, we referred to Cambi (1999), among others. Our research had as locus the Mathematics Course of the CCEN/UFPB. Our research instruments were: field diary, questionnaires, classroom observation and semi-structured interview. Students from the 3rd, 5th and 7th periods, totalizing 164, answered the questionnaire as well as the 05 professors most mentioned by them. We observed 05 classes from these professors and interviewed the coordinator of the course. We take into consideration that it is necessary to discuss and introduce the theme of the university pedagogy in such a way that the university professors transform their pedagogical practices, based on the traditional paradigm, into pedagogical practices sustained by the post-modernity paradigm. Therefore, knowledge, the act of doing and the act of knowing how to do will have as basis the complexity of the professors´ knowledge, the knowledge plurality and the multi-referentiality existent in both the teaching and learning act. In this way, the Education Sciences help to understand the professionalization and the formation of High Education professor. We also understand that this paradigm change undergoes the professor s and the student s continuous formation. Both of them are actors and authors in the teaching learning process as well as builders of the scientific knowledge. So, we present the Continuous Formation Project which we propose to implement with the objective to discuss the University Pedagogy and the academic knowledge inherent to the university professor.